English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-09-19 06:47:11 · 10 answers · asked by exp 1 in Science & Mathematics Mathematics

10 answers

x^2 + 1 is unfactorisable in terms of real numbers.

Possible explanations:
1) You typed the question wrong
If you instead meant "how to factorize x^2 - 1" then it is simple.
The method is called "The difference of two squares"
Since 1 is a square number, and x^2 is (obviously) a square number, you can immediately write it as (x + 1)(x - 1)
This causes the term in x to cancel. Expand the brackets if you're not convinced.

2) You need an answer in terms of imaginary numbers.
While it is true that there are no real roots of the equation x^2 + 1 = 0, there ARE imaginary ones.
Substitute the correct coefficients into the quadratic formula and you will find that the roots of the equation are at +i and -i respectively, where i is the imaginary number sqrt(-1).

From this, we can immediately see that the eqation factorises into (x + i)(x - i) just like the difference of two squares method. Multiply this out if you need convincing, remembering that i^2 = -1.


Hope this helps!

2006-09-19 07:03:01 · answer #1 · answered by ? 3 · 0 0

In general, considering imarginary as well as real coefficients, the factorisation is as follows:
x^2 + 1
= x^2 - i^2
= (x + i)(x - i)

However, with the additional restriction of all the coefficients of the exponents in x being strictly real, the factorisation would be:

x^2 + 1
= (x+1)^2 - [sqrt(2x))] ^2
= [x+sqrt(2x) +1][x-sqrt(2x)+1]

2006-09-19 07:16:03 · answer #2 · answered by K Sengupta 4 · 0 0

by x2+1 do you mean x^2 + 1 or x^(2+1) or 2x + 1 or somehting else?

2006-09-19 07:03:33 · answer #3 · answered by richard457 4 · 0 0

In the universe of the real numbers it can't be done.

If x exists in the imaginary plane, then x^2 + 1 = (x + i)(x - i).

2006-09-19 06:54:36 · answer #4 · answered by kooshman38 3 · 0 0

Use the quadratic formula. However - it seems to me that you will only be able to factor this expression if you are open to using imaginary numbers. Limiting yourself to only the real numbers will result in no solution, I do believe.

2006-09-19 06:58:20 · answer #5 · answered by captain2man 3 · 0 0

expensive Clouie, x^(2)-a million The binomial could be factored utilising the version of squares formula, simply by fact the two words are appropriate squares. the version of squares formula is a^(2)-b^(2)=(a-b)(a+b). (x-a million)(x+a million) ================= 3x^(2)+12x+9 element out the GCF of three from each and every term interior the polynomial. 3(x^(2))+3(4x)+3(3) element out the GCF of three from 3x^(2)+12x+9. 3(x^(2)+4x+3) For a polynomial of the kind x^(2)+bx+c, locate 2 factors of c (3) that upload as much as b (4). in this difficulty 3*a million=3 and 3+a million=4, so insert 3 simply by fact the impressive hand term of one element and a million simply by fact the impressive-hand term of the different element. 3(x+3)(x+a million) ======================== x^(4)-a million The binomial could be factored utilising the version of squares formula, simply by fact the two words are appropriate squares. (x^(2)+a million)(x^(2)-a million) The binomial could be factored utilising the version of squares formula, simply by fact the two words are appropriate squares. the version of squares formula is a^(2)-b^(2)=(a-b)(a+b). (x^(2)+a million)(x-a million)(x+a million)

2016-10-17 06:53:42 · answer #6 · answered by freudenburg 4 · 0 0

multiply the value of x times 2 and then add one

example: if x = 5

5 x 2 + 1
10 + 1
11

Is this what you meant?

2006-09-19 06:55:37 · answer #7 · answered by DB Cash 4 · 0 0

that can't be done without imaginary numbers.

if you possible meant x2-1 then its (x+1)(x-1)

otherwise you have incorporate "i" which i forget how to do.

2006-09-19 06:56:11 · answer #8 · answered by Anonymous · 0 0

we could do it in the imaginary plane remembering that
i=(-1)1/2 and i^2=-1
x^2+1
=x^2-i^2
=(x+i)(x-i)

2006-09-19 07:08:00 · answer #9 · answered by openpsychy 6 · 0 0

2x+1 is already factored.

2006-09-19 06:54:34 · answer #10 · answered by Rance D 5 · 0 0

fedest.com, questions and answers